Ausiàs March, en anglès i en prosa - Archer, Robert (Caplletra. Revista Internacional de Filologia, 2006)
In this study we analyze the English translations of Ausiàs March already carried out (Terry, Conejero-Ribes-Keown, Wittlin and Archer), and we pay attention to the criteria and the solutions used. Here the emphasis is on those questions related to the lexicosemantic choice that determines the general strategy of the new translation into prose that the author of this study has carried out for IVITRA. The article is also concerned about the interaction between translation and the improvement of the knowledge of the original itself, as a consequence of translating it and having to understand it completely, even up to the point of proposing some amendments to the criticophylologic fixation.